Cars, energy, nuclear diplomacy and the law : cars, energy, nuclear diplomacy and the law : a reflective memoir of three generations - Smith, John Thomas, 1943- (Rowman and Littlefield Publishers, Inc., 2012)
This multigenerational memoir sketches the lives of three generations of the author's family that were involved with some of the most profound issues of the twentieth century. With a paternal grandfather present at the creation of General Motors Corporation, a maternal grandfather who was a natural gas pipeline pioneer, and a father who worked to constrain the nuclear arms race between the United States and Russia and to curtail proliferation of nuclear weapons.